ADAPTASI POHON API-API (Avicennia marina) UNTUK MEMPERTAHANKAN HIDUPNYA DI HUTAN MANGROVE KECAMATAN KUSAN HILIR KABUPATEN TANAH BUMBU KALIMANTAN SELATAN - Rahmad Robianto; Gusti Muhammad Hatta; Eva Prihatiningtyas (Jurnal Sylva Scienteae, 2020)
The aim of this research is to know the difference of roots physical form of A marina in inundated and non inundated Mangrove forest in order to maintain their life. The research is carried out by purposive sampling in order to get inundated and non inundated sites. Direct observation is done on the root physical form on both sites. Based on the observation that roots of A marine in inundated site show that the number of long roots relative higher in inundated than in non inundated siteKeywords: Avicennia marina; breath root; inundated; not inundated